Development of a Standardized Peripheral Nerve Block Procedure Note Form. Issue 1 (1st January 2005) - Gerancher, J. C.; Viscusi, Eugene R.; Liguori, Gregory A.; McCartney, Colin J.; Williams, Brian A.; Ilfeld, Brian M.; Grant, Stuart A.; Hebl, James R.; Hadzic, Admir
Abstract : Objectives: Despite the tremendous growth of peripheral nerve blocks, no standard format exists to document their performance. Our objective was to create a peripheral nerve block form based on key elements of literature evidence and on our own group consensus. Results: We describe the process and results of our multi-institutional effort to construct a standardized peripheral nerve block procedure form. Conclusion: A form was developed to help meet the medical, legal, and billing requirements of documentation consistent with the performance of peripheral nerve block.